POLITICAL RISK GOVERNANCE THROUGH THE PRISM OF NATIONAL SECURITY POLICY OF UKRAINE - Antypenko , I. (Theory and Practice of Public Administration, 2020)
The article is devoted to the assessment of the Ukrainian state’s efforts regarding the integration of political and other national risk management activities into the process of making strategic political and administrative decisions, primarily in the sphere of national security. The work analyzes the latest legal and regulatory framework in this area, as well as the functioning of sectoral systems of crisis response. It is shown that the current legal framework continues to reproduce a reactive state policy in the area of national security.The study concludes that the development of risk-oriented public policy in Ukraine is currently limited to the security and defense sector, and only in two directions. In first direction, the appropriate policy develops by supporting state strategic planning through activities on monitoring and evaluation of national security. The second, by modernizing the institutional support of crisis management through the formation of a hierarchically structured network of situational and crisis centers.It is proved that real work on introducing elements of political risk governance into the state’s strategic planning structure by implementing reviews (analysis) of the security and defense components remains is extremely slow and still ineffective.The author highlights the history of attempts to create in Ukraine a system of risk governance in the form of strategic-level crisis centers – the situational centers network. He characterizes the sectoral situational centers or permanent bodies that perform functions specific to them.However, due to the outdated sectoral approach to crisis prevention and response, traditionally insufficient funding and the inadequate technical support of this institution, the establishment of an effective state crisis response system is significantly slowed down.